Handbook of research on digital content, mobile learning, and technology integration models in teacher education - Keengwe, Jared, 1973- (2017)
"This book provides a wide range of frameworks to help teacher educators and other researchers examine the benefits, challenges, and opportunities for using mobile technology, digital content and technology integration in teacher education"--
Universal design for learning (UDL) guidelines for mobile devices and technology integration in teacher education / Neal Shambaugh and Kimberly Floyd -- Using the COVA approach to promote active learning in digital learning environments / Cindy Cummings, Dwayne Harapnuik, and Tilisa Thibodeaux -- Case study : preparing students for active engagement in online and blended learning environments / Sophia Palahicky and Adrianna Andrews-Brown -- Questioning the role of tomorrow's teacher : technology facilitated differentiated learning in 21st century classrooms / Doug Reid and David Feist -- An integral analysis of teachers' attitudes and perspectives on the integration of technology in teaching / David Ikenouye and Veronika Bohac Clarke -- Integrating technology in the postgraduate certificate in higher education in Namibia : is it an effective tool for professional development? / Katherine Carter, Michelle Maree, and Geoffrey Shakwa -- Choosing and adapting a mobile learning model for teacher education / Bonface Ngari Ireri, Ruth Diko Wario and Irene Mukiri Mwingirwa -- Different enhanced-technology used in core counselor education courses : what are they and their effectiveness? / Levette S. Dames and Jennifer Barrow -- Technology integration in digital learning environments / Irene Mwingirwa Mukiri and Bonface Ngari Ireri -- Applications of artificial intelligence in assessment for learning in schools / Subhagata Chattopadhyay, Savitha Shankar, Ramya. B. Gangadhar and Karthik Kasinathan -- Enhancing learner-driven informal learning in a virtual practice community : the Massive Open Online Course (MOOC) as a learning solution for professional development / Chungil Chae, Boyung Suh, Seung-hyun Han, Heeyoung Han and Doo Hun Lim -- Technology and digital content : promoting learner-centered pedagogy / Maureen N. Short -- Effective educational leadership in the digital age : an examination of professional qualities and best practices / Kwesi Armah Tandoh and Josephine Effibah Ebe- Arthur -- Towards a framework and learning methodology for innovative mobile learning : a theoretical approach? / Ebba Ossiannilsson?and Nicolas Ioannides -- Best practice to support online student engagement / Lorie Cook-Benjamin -- Online instruction : is the quality the same as face to face instruction? / Zandile P. Nkabinde -- Implementing a measurement framework to assess and evaluate student readiness for online learning and growth / Kelly D. Bradley, Heather Arrowsmith and Richard Mensah -- Integrating ICT in secondary teacher education : cae of Malwai's education policy texts since 1994 / Foster Gondwe -- Adoption and use of innovative mobile technologies in Nigerian academic libraries / Awoyemi, Robert Akinade -- Integrating digital learning strategies with students at the historical black college/university (HBCU) / Audrey McCrary Quarles, Cassandra Sligh Conway, Stanley Harris, James Osler and Leslie Rech.
Includes bibliographical references and index.
Keywords: Teachers -- Training of -- Technological innovations; Teachers -- Training of -- Research; Educational technology